Biological effects of phytoestrogens: clinical effectiveness and potential application in the treatment of climacteric syndrome - M. A. Chernyavskaya; I. A. Narkevich (Фармакоэкономика, 2020)
Aim. To review scientific publications on clinical effectiveness and potential application of phytoestrogens (PE) in the treatment of climacteric syndrome.Materials and methods. The PRISMA approach was used. The systematic search was performed in three electronic scientific databases: Cochrane library, PubMed/MEDLINE, and eLIBRARY.ru. The publications were also manually searched for in the reference lists of the relevant articles.Results. The filters were used to select 79 publications; 26 of them were included in the final review. The main method of treatment for the manifestations of the climacteric syndrome is menopausal hormonal therapy (MHT). One of the alternative methods for the control of its symptoms is the application of phytoestrogens (PE), primarily, isoflavones, lignans, and coumestans. Active metabolites of PE are expressed under the influence of gut microflora that is different in various groups of women, which can determine the differences in the effectiveness. Taking into account multidirectional character of the studies as well as numerous publications of low quality, it is still impossible to come to the final conclusion on the effectiveness of PE-containing food supplements (FS) when it comes to a decrease in the occurrence rate and expression of such symptoms as hot flushes, night sweats, and cognitive deterioration. The conclusions on the prevention of cardio-vascular diseases are not definite either.Conclusions. The review showed that scientists could not come to the conclusion on the effectiveness and safety of PE-containing FS. Probably, the most prospective means of the control of climacteric syndrome are FS that contain isoflavones of red clover and soy in the maximum effective concentration. Considering free access to such FS on the market, they must meet high safety requirements.